Wizerunek średniowiecznego Żyda - Jaroszewska, Anna (ETHICS IN PROGRESS, 2014)
Medieval Jews were perceived by their neighbors in two ways. On the one hand, as an integral part of the community, living among Christians, leading business or cooperating intellectually with them. Jewish philosophers were known and respected by Christian thinkers, like the Jewish medics - prized for centuries for their extensive knowledge and skills. On the other hand, the medieval Jew is a clever merchant, cunning moneylender that is gathering his fortune, follower a foreign religion - full of incomprehensible mysterious rituals. Although there was no shortage of sympathy, Jews were rather approached with distrust and distance. A perfect example of this is the ghetto, created in medieval times. Medieval Jew's pictures are multidimensional and very interesting. The article offers an attempt to present this diversity, discussing the Jew as a merchant, usurer, a resident of the ghetto, dissenter and a member of medieval society.